2003
DOI: 10.1126/science.1090163
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Silica-Carbonate Structures and Detection of Ancient Microfossils

Abstract: We have synthesized inorganic micron-sized filaments, whose microstucture consists of silica-coated nanometer-sized carbonate crystals, arranged with strong orientational order. They exhibit noncrystallographic, curved, helical morphologies, reminiscent of biological forms. The filaments are similar to supposed cyanobacterial microfossils from the Precambrian Warrawoona chert formation in Western Australia, reputed to be the oldest terrestrial microfossils. Simple organic hydrocarbons, whose sources may also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
307
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(330 citation statements)
references
References 23 publications
15
307
1
2
Order By: Relevance
“…However, the combination of biological, chemical, and physical factors during taphonomic processes and deep burial inevitably alter the chemical, structural, and isotopic fidelity of such fossilized biosignatures (Schiffbauer et al 2007). In addition, abiogenic processes may form disordered carbondominated precipitates displaying morphologies and signatures quite similar to biogenic objects (García-Ruiz et al 2003;Pasteris and Wopenka 2003;McCollom and Seewald 2006). Therefore, unambiguously identifying biosignatures within metamorphic rocks has been generally believed to be extremely difficult, if not impossible, except in very rare cases such as the exceptionally wellpreserved Burgess Shale ▶ fossils which experienced greenschist facies metamorphism (Powell 2003).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination of biological, chemical, and physical factors during taphonomic processes and deep burial inevitably alter the chemical, structural, and isotopic fidelity of such fossilized biosignatures (Schiffbauer et al 2007). In addition, abiogenic processes may form disordered carbondominated precipitates displaying morphologies and signatures quite similar to biogenic objects (García-Ruiz et al 2003;Pasteris and Wopenka 2003;McCollom and Seewald 2006). Therefore, unambiguously identifying biosignatures within metamorphic rocks has been generally believed to be extremely difficult, if not impossible, except in very rare cases such as the exceptionally wellpreserved Burgess Shale ▶ fossils which experienced greenschist facies metamorphism (Powell 2003).…”
Section: Overviewmentioning
confidence: 99%
“…However, fossilized biosignatures are not immutable but prone to degradation during diagenesis and ▶ metamorphism and may become difficult to distinguish from signatures of abiogenic compounds (e.g., García-Ruiz et al 2003;Pasteris and Wopenka 2003;McCollom and Seewald 2006). Nevertheless, from the multiscale characterization of organic-rich ▶ metamorphic rocks using advanced synchrotron-based micro ▶ spectroscopy techniques, Bernard et al (2007Bernard et al ( , 2010 have shown that high-grade metamorphism might not totally erase structural and chemical bio-features, at least at the sub-micrometer scale.…”
Section: Definitionmentioning
confidence: 99%
“…The biogenicity of stromatolites older than 3.2 Ga 1 is unclear [2,3,4,5]. If they are indeed biotic, they are the oldest morphological evidence for life, now that the identification of 3.3 to 3.5 Ga microfossils [6] has been challenged [7,8]. Here we propose a mathematical model for stromatolite morphogenesis that endorses a biotic origin for coniform stromatolites.…”
Section: Introductionmentioning
confidence: 99%
“…Known abiotic products that can mimic life morphologies or chemistries include vesicles made in the laboratory from meteoritic kerogen or in other prebiotic chemistry experiments (e.g., Deamer et al 2006), fluid inclusions, carbonaceous filamentous shapes resulting from migrating organic matter (with carbon isotopic fractionation resembling life patterns) around minerals casts in hydrothermal environments (Brasier 2005;Brasier et al 2006), aggregates of silica spheres and rods in silica-rich waters of hydrothermal springs, migration of carbonaceous materials along microfractures (VanZuilen et al 2007), within or around silica (e.g., Jones and Renaut 2007;Lepot et al 2009b). Finally, mineralized pseudo-fossils have been produced using a mixture of barium carbonate and silica in laboratory experiments (Garcia-Ruiz et al 2003). The resulting auto-assembling segmented filaments contain organic matter.…”
Section: Overviewmentioning
confidence: 99%